Anaerobic co-digestion of chicken manure with energy crop residues for biogas production. Issue 1 (May 2021) - Dawi Cahyono, N.A; Shamsuddin, M.R.; Ayoub, M.; Mansor, N.; Isa, N.H.M.; Nagoor Gunny, A.A
Abstract: Biogas or bio-methane is an alternative energy source produced by anaerobic digestion (AD) technology whereby the organic matter is degraded by naturally present microorganisms and converted into a combustible gas. This paper focus on the utilization of anaerobic codigestion (AcoD) method since biogas yield so far remains minimum based on mono-digestion alone due to low energy content. In this work, empty fruit bunch (EFB), oil palm frond (OPF) and sugarcane bagasse (SB) are being used as co-digestion additive since energy crop residues are known for its high carbon and energy content to enhance the process. A series of five 1.5L reactors were set up for a mesophilic condition at temperature 40°C, with initial pH range of 7-8, for 60 days of retention time. The mono-digestion reactor of chicken manure is labelled as DC1, and the co-digestion reactors with sugarcane bagasse, OPF and EFB are labelled as DSB, DOPF and DEFB, respectively. The recorded C/N ratio of co-digestion reactors were improved to be in a favourable range of 15 to 35 with DSB being the highest at 17.74 compared to that of control reactor at 11.35. As a result, total biogas production for DSB increases up to 36% due to its significantly high carbon content from sugarcane bagasse that provide stability for the bacterial growth and its activities. Sugarcane bagasse act as a good carbon source for the AD system, thus enhance the methane production. On the other hand, DOPF and DEFB give 13% and 41% lesser total biogas volume, however, produces much higher methane concentration compared to the control reactor. This shows that DOPF and DEFB give a higher methane yield which defines the more stability and efficiency of digestion process.